AN ANALYTICAL STUDY OF MAHATMA GANDHI RURAL EMPLOYMENT - UMESH KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
This was a problem because of the necessity to meet both of these requirements simultaneously. The Jawahar Rojgar Yojana (JRY) was initiated the same year that NREP and RLEGP were combined into a single program. This brand-new wage employment program was significantly unlike to the ones that had been implemented in the past since it placed an emphasis on reorganizing the delivery mechanism through Panchayati. Raj Institutions (PRIs). Gram Panchayats (GP), Panchayat Samities, and District Rural Development Agencies (DRDA)/Zila Parishads each received their allotted portion of the funds in the proportion of 70:15:15 respectively.